Protein synthesis in muscle measured in vivo in cachectic patients with cancer. Issue 6445 (8th September 1984) - Emery, P W; Edwards, R H; Rennie, M J; Souhami, R L; Halliday, D
Abstract : Rates of synthesis of protein were measured in vivo in skeletal muscle and in the whole body of cachectic patients with cancer and in normal healthy men, using a tracer infusion of leucine labelled with a stable isotope. Synthesis of protein in muscle was significantly reduced in the patients with cancer (0.030 v 0.198%/hour; p less than 0.01), whereas whole body rates of protein synthesis and degradation did not differ significantly between the two groups. Thus depression of synthesis of protein in muscle appeared to be the immediate cause of muscle wasting in cancerous cachexia. Any therapeutic intervention that aims at preventing the onset of cachexia should be designed to stimulate the synthesis of protein in muscle, and measurement of turnover of protein may be used to evaluate such treatment provided that rates of protein synthesis are measured directly in specific tissues.